Scaffolding EFL Learners English Literacy Through Extensive Reading - Muhamad Sofian Hadi; Gitazania Putri (Ethical Lingua: Journal of Language Teaching and Literature, 2021)
The purpose of this article is to find out how the Extensive Reading approach affects EFL learners' reading literacy. The research sample consisted of 37 eighth-grade students from SMP PARIGI. The writer chose the sample using a random sampling technique. The author employed quantitative research with a quasi-experimental design that included a pre- and post-test. The pre-test mean for students is 57.16, while the post-test mean for students following therapy is 81.21. The outcome of the T-test is -2.50, with a degree of significance of 5% (=2.028). Extensive Reading, in other words, has an impact on students' reading literacy.